A SHEAR TEST OF DEBRIS ROCK AT LABORATORY SCALE - Saviqri Suryaputra; Made Astawa Rai; Nuhindro Priagung Widodo; Bob Andrea Lingga (Puslitbang tekMIRA, 2020)
As one of rock’s mechanical properties, the shear strength is one of the most significant factors that affect rock-dump slope stability. On previous research, one of the tests that needs to be conducted for shear strength characteristic estimation is the field-scale tilt test that requires a lot of expense and material. In this research, a direct shear test was conducted to 3 different mudstone specimens for modeling the Barton and Kjaernsli shear strength at laboratory-scale, using the fragment size of coarse (50 mm - 1 mm), medium (<1 mm – 0.25 mm), and fine (<0.25mm). Then, the results was compared to the shear strength of the debris rock that was come from the value of the equivalent roughness (R) both derived from back-calculated and empirical calculation. This research delivers the estimated shear strength that is more representative because the specimens were controllable in regards to its fragment size and composition. The more predominant big rock fragment in a composition, the bigger its back-calculated R-value. The obtained crushed rock shear strength with empirical R was lower in value compared to the one with back-calculated R.